THE EFFECTIVENESS OF THE TREATMENT AND PREVENTION OF PARVOVIROSIS ENTERITIS OF DOG IN CONDITIONS OF VETERINARY CLINICS LLC «BIOCENTER» IN CITY POLTAVA - Коне, М. С.; Романова, А. Л. (Scientific Progress & Innovations, 2017)
We studied the age and pedigree sensitivity, seasonal occurrence and dynamics of display of parvovirosis enteritis in conditions of veterinary clinics LLC «Biocenter» in city Poltava. We established that enzootic of parvovirosis enteritis distemper is often seen in spring and summer, dogs of German shepherd breed are more likely to be infected. According to parvovirosis enteritis distemper we developed and offered treatment regimen of intestinal form which is much more effective than the conventional basic method. The importance of the use of chemotherapeutic agents at some stages of infection is substantiated. We established that «Nobivak DHPPI» is proved as the most effective vaccine for the prevention of plague in dogs.